DO ENVIRONMENTAL, SOCIAL, GOVERNANCE, AND GREEN INTELLECTUAL CAPITAL BOOST FINANCIAL PERFORMANCE THROUGH CAPITAL STRUCTURE? - Dian Widiyati; Riyan Harbi Valdiansyah; Faith Njaramba (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) and Green Intellectual Capital on corporate financial performance, with capital structure as a moderating variable. It is motivated by increasing stakeholder attention to sustainability practices and inconsistent empirical findings regarding their financial implications. Using a quantitative explanatory approach, this study analyzes panel data from 14 companies listed on the Indonesia Stock Exchange that consistently published annual and sustainability reports during the 2019–2023 period. The data were analyzed using Moderated Regression Analysis after passing classical assumption tests. The results indicate that ESG disclosure has no significant effect on financial performance. In contrast, Green Intellectual Capital has a positive and significant effect on financial performance. Capital structure also shows a positive and significant impact on financial performance. Furthermore, capital structure does not moderate the relationship between ESG disclosure and financial performance but significantly weakens the effect of Green Intellectual Capital on financial performance. Robustness tests conducted before and after the COVID-19 period confirm the increasing relevance of Green Intellectual Capital in the post-pandemic era. These findings contribute by highlighting the strategic role of green intellectual assets, supported by a sound financing structure, in achieving sustainable financial performance.